CAPACITY BUILDING MELALUI KAJIAN PERDA - Zaelani, Zaelani (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
Devices legislation at the local level one of them is localregulation. Local regulations are part of national law, hasan important and strategic position in implementing one ofthe tasks of regional autonomy and the duty of assistance,and outlines legislation higher. Local regulations are basedon local needs in managing their respective areas, localregulations must be principle accommodate justice and publicinterest areas. Regulations prohibited area contrary to thelaws of higher, and prohibited violate the public interest. Inaddition local regulations should be drafted based on legalrequirements and in accordance with the provisions oflegislation, especially Law Number 10 Year 2004 on theFormation of Laws and Regulations. The current inventorylocal regulations, many local regulations are not fully preparedto apply the settings in accordance with the provisions of ActNo. 10 of 2004, based on this reality would need to befacilitated by technical assistance drafting local regulationsconstantly and continuously. Local Regulation FacilitationDirectorate has provided facilitation and mediation in theform of consultation, technical assistance, provision andregulation of data processing areas. One form of facilitationactivities conducted in the form of local regulation studies,so the compilers legislative drafting local regulations canincrease knowledge and understanding of drafting localregulations. It is expected that through the study of regionalregulations, the compilers of local regulations may increasethe knowledge and skills in formulating local regulationsthat more qualified, so that later on there was no localregulations canceled.